Penerapan Metode Bermain Peran Untuk Pengembangan Kreativitas Berfikir Anak Tk Kelompok A Di Tk Khadijah Loceret Nganjuk - Fina Lutfiana Rahmawati (Prodi Manajemen Pendidikan Islam STAI Darussalam, 2018)
The research was aimed to identify creativity development of children through role play method to children group of A , Pre-school Khadijah Loceret Nganjuk, year 2014/2015. The research was class or group experimental research with children group of A as subject. Sum of children is 15 children. The research was collaborative between researcher, teacher and headmaster. The data was collected by observation, interview and documentation process. The validity of data was verified by triangulation technique. The data was analyzed by comparison technique, which compares result obtained by children with performance indicators. The result shows that linguistic ability of children develops in every step or circle. The creativity develops from pre-circle (50%) to circle I (51%), circle II (60%) and circle III (80%). The conclusion of this research is the creativity of children can develop through treatment of role play method in school activity